Confronting the expanse of data education: From local open data to global cyberinfrastructure. Issue 1 (1st February 2019) - Palmer, Carole; Greenberg, Jane; Lin, Xia; Howison, James; Weber, Nicholas; Oh, Sam; Murillo, Angela
ABSTRACT: As the demand for data science and data‐intensive capabilities grows in all sectors, educators in schools of information and library and information science are working to deepen and expand their programs to meet workforce expectations. This panel will examine current trends and investments in data education and professionalization, with an emphasis on the unique contributions information professionals bring to the data workforce. Educators will present on current initiatives that represent the breadth and complexity of preparing information professionals for work in data intensive environments. Their unique approaches anticipate and respond to workforce demand, address significant educational challenges, and offer models for making progress within the varying contexts of schools in different regions of the U.S. and Asia. Half of the session will be reserved for audience engagement designed to leverage and share the wealth of experience of the educators and students in attendance. The exchange will generate ideas about new directions and successful approaches that educators can apply to set priorities, position their programs, and collaborate to enrich and provide leadership in data education.